Comparison of genetic diversity and population structure of Saccostrea mordax lineages A, B, and C across South China Sea and Celebes Sea - Yinjie Zhang; Yinjie Zhang; Yinjie Zhang; Yinjie Zhang; Haitao Ma; Haitao Ma; Haitao Ma; Haitao Ma; Haitao Ma; Haitao Ma; Chenghui Han; Chenghui Han; et al. (Frontiers in Marine Science)
Saccostrea mordax is an ecologically important bivalve species and a potential genetic resource for oyster breeding that inhabit in the Indo-Western Pacific region, characterized by three distinct lineages: A, B, and C. However, limited information is available about its genetic variation and genetic structure. The present study was conducted to study genetic diversity and population structure of S. mordax lineages A, B, and C based on mitochondrial COI gene data across the South China Sea and Celebes Sea. The UPGMA phylogenetic tree among populations, BI phylogenetic tree among individuals and median network revealed three main clusters, corresponding to S. mordax lineages A, B, and C. The results of K2P sequence divergence, pairwise Φst, gene flow and AMOVA indicated clear genetic differences among the lineages, combined with sympatric in all 7 geographical populations, these suggests lineages A and B are transitional periods of new species formation. Moreover, different patterns of population subdivision were found within lineages A, B and C. In lineage A, significant genetic differentiation was only observed between YM (Celebes Sea) and other populations (South China Sea), with a significant correlation between geographical distance and genetic distance among populations. In lineages B and C, there was no genetic differentiation between YM (Celebes Sea) and other populations (South China Sea), and no significant correlation between genetic distance and geographical distance among populations. The population history analyses indicated that populations of lineage A have experienced a recent sudden expansion, while populations of lineages B and C were large stable. These findings are essential for the conservation, sustainable utilization, and ecological restoration of S. mordax.